Restoration of impaired nitric oxide production in MELAS syndrome with citrulline and arginine supplementation - El-Hattab, Ayman W. (2012)
Mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) syndrome is one of the most common mitochondrial disorders. Although the pathogenesis of stroke-like episodes remains unclear, it has been suggested that mitochondrial proliferation may result in endothelial dysfunction and decreased nitric oxide (NO) availability leading to cerebral ischemic events. This study aimed to assess NO production in subjects with MELAS syndrome and the effect of the NO precursors arginine and citrulline. Using stable isotope infusion techniques, we assessed arginine, citrulline, and NO metabolism in control subjects and subjects with MELAS syndrome before and after arginine or citrulline supplementation. The results showed that subjects with MELAS had lower NO synthesis rate associated with reduced citrulline flux, de novo arginine synthesis rate, and plasma arginine and citrulline concentrations, and higher plasma asymmetric dimethylarginine (ADMA) concentration and arginine clearance. We conclude that the observed impaired NO production is due to multiple factors including elevated ADMA, higher arginine clearance, and, most importantly, decreased de novo arginine synthesis secondary to decreased citrulline availability. Arginine and, to a greater extent, citrulline supplementation increased the de novo arginine synthesis rate, the plasma concentrations and flux of arginine and citrulline, and NO production. De novo arginine synthesis increased markedly with citrulline supplementation, explaining the superior efficacy of citrulline in increasing NO production. The improvement in NO production with arginine or citrulline supplementation supports their use in MELAS and suggests that citrulline may have a better therapeutic effect than arginine. These findings can have a broader relevance for other disorders marked by perturbations in NO metabolism.